2004
DOI: 10.1002/anie.200351975
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and [60]Fullerene Complexation Properties of Azacalix[m]arene[n]pyridines

Abstract: Remarkably stable C60 and C70 complexes with stability constants Ks of 70 680±2060 and 136 620±3770 M−1, respectively, are formed by azacalix[4]arene[4]pyridine 1. The smaller‐ring‐homologue azacalix[2]arene[2]pyridine and compound 1 were readily synthesized, and they adopt a heavily twisted 1,3‐alternate and a 1,2,3‐partial cone conformation, respectively, in the solid state (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(92 citation statements)
references
References 66 publications
4
86
0
2
Order By: Relevance
“…[20] The preparation of derivatives 10 a and 10 b (Figure 4) is remarkably straightforward; they are both obtained in three steps starting from 1,3-diaminobenzene and 2,6-dibromopyridine. [21] Unlike 10 b, the addition of 10 a to a C 60 solution does not lead to any color change, thus suggesting that no interaction takes place with the smaller macrocycle 10 a, as was confirmed by UV/Vis and fluorescence titrations. These studies demonstrate that 10 b forms 1:1 complexes with both C 60 and C 70 , and the authors report binding constants of log K sv = 4.8 and 5.1 in toluene at 298 K for C 60 and C 70 , respectively, although they neglect the effect of possible dynamic quenching.…”
Section: Aromatic Heterocycles For Fullerene Recognitionmentioning
confidence: 56%
“…[20] The preparation of derivatives 10 a and 10 b (Figure 4) is remarkably straightforward; they are both obtained in three steps starting from 1,3-diaminobenzene and 2,6-dibromopyridine. [21] Unlike 10 b, the addition of 10 a to a C 60 solution does not lead to any color change, thus suggesting that no interaction takes place with the smaller macrocycle 10 a, as was confirmed by UV/Vis and fluorescence titrations. These studies demonstrate that 10 b forms 1:1 complexes with both C 60 and C 70 , and the authors report binding constants of log K sv = 4.8 and 5.1 in toluene at 298 K for C 60 and C 70 , respectively, although they neglect the effect of possible dynamic quenching.…”
Section: Aromatic Heterocycles For Fullerene Recognitionmentioning
confidence: 56%
“…In this context, host molecules composed of triarylamines should exhibit high affinities for fullerenes in comparison with the corresponding phenol-based receptors. Actually, the K SV values of a dendrimer 19 [36], azacalix [3]arene [3]pyridine 20 [37], and azacalix[n]pyridine 21 (n ¼ 4-9) [38] are considerably high (K SV for 19ÁC 60 ¼ 180000 AE 80000 Â 10 5 M À1 , K SV for 20ÁC 60 ¼ 70680 AE 2060 M À1 , and K SV for 20ÁC 70 ¼ 136620 AE 3770 M À1 ) (Figure 3.9). The participation of additional attractive CT interaction should play an important role in the complexation.…”
Section: Modified Traditional Host Moleculesmentioning
confidence: 99%
“…[7] While the diversity is still limited relative to those of carbon-and sulfur-bridged calixarenes, intriguing complexation properties based on the introduction of nitrogen atoms as the bridging units have thus far been disclosed. [8][9][10] For instance, Wang reported that azacalix [m]arene[n]pyridines exhibited much greater complexation ability for fullerenes C 60 and C 70 , relative to those of other mono-macrocyclic receptors reported to date.…”
Section: Introductionmentioning
confidence: 99%